Openness towards mental illness in Malaysia - Ulka Chandini Pendit,; Koo, Ah Choo (Penerbit Universiti Kebangsaan Malaysia, 2020)
Mental health is an important component for well-being beside physical health. Recent years, mental illness has become a challenge in society. However, public stigma towards mental illness is very bad. This stigma makes people with mental illness have difficulty to recover and to get help from society. This paper reports the evidences gathered through the recovered patients themselves of the importance of openness towards mental illness and the need for removal of stigma towards mental illness. There were six interviewees participated in a study conducted in a non- governmental organization (NGO) that supports mental wellness at Petaling Jaya City. The permission of interview was granted by the NGO’s management and also the participants. The data gathered was open-ended answers addressing questions which are related to their feeling, public perceptions and also their expectation of the society and supports provided by external parties such as government. The results of the study show that the perception towards mental illness patients should be more open and receptive. Supports and reception given to them is crucial. Public and government should work together to build a mentally healthy and supportive environment for a better society.